The Impact of the Filipino Plate Method versus Standard Nutrition Education on Food Group Proportions and 2-hour Postprandial Blood Glucose for Type 2 Diabetes - Montevirgen, Richultz; Mendoza, Kristine Bea; Lopez, Lizette Kristine (Journal of the ASEAN Federation of Endocrine Societies, 2022)
<center></center><center></center> Objectives. To compare the efficacy of the Filipino plate method against standard nutrition education in the selection of food group proportions and in reducing 2-hour postprandial blood glucose levels (2h-PPG) among patients with type 2 diabetes. Methodology. This randomized, open-label trial assigned 148 subjects with type 2 diabetes to receive nutrition education using either the Filipino plate method or standard nutrition education, as recommended by the American Diabetes Association (ADA). The subjects were given meals before and three days after the intervention, at which time the contents of their plate were scored based on food group proportions. After the meal, 2h-PPG levels were obtained. Pre- and post-intervention plate scores and 2h-PPG were compared in both groups. Results. Plate scores were significantly increased from pre to post-teaching for both groups (p value <0.001). There was no statistically significant difference in post-teaching scores between the two modes of nutrition education (Filipino plate method median score 8/9 vs standard nutrition education 7/9, p=0.018). The 2h-PPG results decreased significantly from baseline to post-teaching for both groups (p=0.008). There was no significant difference in the reduction in 2h-PPG between the two groups (p=.741). Conclusion. The Filipino plate method was comparable to standard nutrition education in improving food group choices and proportions as well as 2h-PPG in patients with type 2 diabetes.